Royal Canadian Mounted Police: Three Patrols Made in the Canadian Arctic in 1934 (Polar Record, 1935)
This patrol—which was made through comparatively untravelled country, and which was the first police patrol undertaken between the Red Rock Lake district, due east of Great Bear Lake, North-west Territories and Bathurst Inlet—would have been a difficult one under ordinary conditions of spring travel. It was, however, carried out in mid-winter, when travelling conditions were exceptionally severe; and the party covered 700 miles during 37 days.